Evaluation of Rapid Diagnostic Tests for Assessment of Hepatitis B in Resource-Limited Settings - James S. Leathers; M. Belen Pisano; Viviana Re; Gertine van Oord; Amir Sultan; Andre Boonstra; Jose D. Debes (Annals of Global Health, 2019)
Chronic Hepatitis B (HBV) is the most important cause of liver disease worldwide. There is a need for low-cost tests to aid in diagnosis and management of HBV infection in resource-limited settings. We evaluated the utility of several rapid diagnostic tests (RDT) in three different continents (Europe, South America, Africa). The HBsAg RDT showed optimal sensitivity and specificity. The anti-HBeAb RDT showed acceptable sensitivity and excellent specificity. Our results suggest that these RDTs could be used for screening and management of HBV.